The Impact of Social Media Influencers and Brand Awareness that Effects to Consumer’s Purchasing Decision on Social Media Platforms in Bangkok - Songmuang, Suntree (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were to; 1) study the importance of social media influencer, 2) study the importance of brand awareness, 3) study the importance of purchasing decision on social media platforms, 4) study impact of the social media influencer that effects to consumer’s purchasing decision on social media platforms, and 5) study impact of brand awareness that effects consumers’ purchasing decision on social media platforms. The collected data were chosen by cluster random sampling, and gathered from 400 samples of consumers in Bangkok. The researcher collected the data by using questionnaires. Statistics used for analysis were frequency, percentage, mean, standard deviation, and Multiple Regression Analysis. The results of the research showed that: 1) All of 7 groups of social media influencers are highly important, actor and actress was highest. 2) All of the 5 items of brand awareness are highly important, Brand Associations was highest. 3) The best platform was Facebook that consumers in Bangkok were chosen to buy products. 4) The social media influencers that effected to consumer’s social media platforms in Bangkok were Sport Figure Beauty and High-So. 5) The consumer’s brand awareness that effected the purchasing decision of consumers in Bangkok was brand quality and brand associations was statistically significant at the .05 level.